Premium travel barometer 2016 - Gieschen, Jörn (IE Fundation, 2016)
The Premium Travel Barometer is a new initiative from the IE Premium and Prestige Business Observatory in 2016. The goal of the Barometer is to help better understand the importance of relevant topics for successful business performance in the premium and luxury travel markets. 2016 will be the initial version and the Barometer will be done annually in order to detect trends and changes regarding the analyzed industry drivers. More precisely, the objectives of the Barometer are:  Understand the relevance of selected issues for business success in the premium and luxury travel segment according to selected international industry experts  Uncover the major implications of the chosen topics on the sector development The study has been conducted in two phases and with two different methods. In Phase 1, over 70 international premium travel market experts have been asked to rate 25 selected topics moving the sector, allowing for a ranking of the most important topics for the sector. In Phase 2, a group of premium travel experts was invited to interpret the results of the survey, discuss different aspects of the chosen topics, and identify possible impacts and actionable items. The 25 topics to choose from have been identified in internal discussions among the Barometer collaborators, aiming to create a list representative of the most important topics influencing the business. Different categories of topics were chosen in order to find a somewhat balanced approach.
Keywords: Barometer; relevant topics; successful business performance; luxury travel markets